2013
DOI: 10.1093/conphys/cot017
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal influences on the physiological condition of invasive silver carp

Abstract: This study quantified the nutritional and stress physiology of invasive silver carp across broad spatial and temporal scales to define how these fish interact with their environment. Results demonstrated that nutritional properties varied significantly across rivers and sampling time. Stress levels varied only across time periods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 82 publications
0
11
0
Order By: Relevance
“…• Bioenergetic and nutritional constraints approximate the energetic and metabolic costs associated with introduction to a new habitat and can be used to predict the invasive range of non-native species Liss et al (2013) Goedkoop et al…”
Section: Bioenergetics and Nutritionmentioning
confidence: 99%
“…• Bioenergetic and nutritional constraints approximate the energetic and metabolic costs associated with introduction to a new habitat and can be used to predict the invasive range of non-native species Liss et al (2013) Goedkoop et al…”
Section: Bioenergetics and Nutritionmentioning
confidence: 99%
“…Although we only sampled one known location of bigheaded carps' hybrids at one single point in time, it was from a location known to contain a high proportion of bigheaded carps and their hybrids (Lamer et al 2015). Nutritional trends for bigheaded carps may differ under varying environmental conditions and across seasons (Liss et al 2013); however, the nutritional parameters selected for this study were chosen because they represent a long-term body energy reserve nutritional component (Wagner & Congleton 2004;Congleton & Wagner 2006). Additionally, a longterm study by Sass et al (2014) observed a strong and consistent pattern between the presence of bigheaded carps and the zooplankton community of the Illinois River.…”
Section: Discussionmentioning
confidence: 99%
“…First, a principal component analysis (PCA) was performed, and principal components (PCs) with eigenvalues 11 were interpreted for analysis (Kaiser 1960). For the FA, these PCs were rotated using varimax rotation on the maximum likelihood solution (Kaiser 1960;Liss et al 2013). Variables with factor loadings 1F0.4F were considered maximal contributors to each factor (Kaiser 1960;Liss et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…After the 25-min confinement in the fish bag, M. salmoides were bled a second time in a manner identical to that of the first before being weighed, measured, fin-clipped to prevent resampling, and released. Immediately following withdrawal, extracted blood samples were spun in a centrifuge for 3 min at 6,000 rpm to separate plasma from erythrocytes (Liss et al 2013). Following centrifugation, the plasma layer was removed and divided into two other microcentrifuge tubes.…”
Section: Field Samplingmentioning
confidence: 99%